Fluctuations in dietary intake during treatment for childhood leukemia: A report from the DALLT cohort. Issue 6 (December 2019) - Ladas, Elena J.; Orjuela, Manuela; Stevenson, Kristen; Cole, Peter D.; Lin, Meiko; Athale, Uma H.; Clavell, Luis A.; Leclerc, Jean-Marie; Laverdiere, Caroline; Michon, Bruno; Schorin, Marshall A.; Welch, Jennifer Greene; et al.
Summary: Background: Acute lymphoblastic leukemia (ALL) is the most common pediatric malignancy. Nutritional morbidities are a persistent problem facing pediatric patients during and after treatment and age-gender groups that are at risk for nutritional conditions have not been clearly identified. Therapy is a contributing factor; however, the role of dietary intake remains largely unknown. Prior to conduct of interventional trials, an understanding of the effects of treatment on fluctuations in dietary intake is necessary. Methods: We enrolled 794 children with ALL in a prospective clinical trial. Dietary intake was collected with a food frequency questionnaire at diagnosis and throughout the course of treatment for pediatric ALL. Reported values were compared to the Dietary Recommended Intake (DRI), and normative values (NHANES). Hierarchical linear models and multilevel mixed-effects ordered logistic regression models were used to evaluate longitudinal changes in dietary intake; independent samples t-test with Bonferroni correction was performed to compare to NHANES. Results: Of the evaluable participants at each timepoint, dietary intake was obtained on 81% (n = 640), 74% (n = 580) and 74% (n = 558) at diagnosis, end of induction phase of treatment, and continuation, respectively. Despite exposure to corticosteroids, caloric intake decreased over therapy for most age-gender groups. Predictive models of excess intake found reduced odds of over-consuming calories (OR 0.738, P < 0.05); however, increased odds of over-consuming fat (OR 6.971, P < 0.001). When compared to NHANES, we consistently found that ≥1/3 of children were consuming calories in excess of normative values. For select micronutrients, a small proportion of participants were above or below the DRI at each time evaluated. Conclusions: Our study suggests that dietary intake fluctuates during treatment for ALL as compared to age-gender recommended and normative values. Improving our understanding of nutrient fluctuations and dietary quality will facilitate subsequent analyses addressing relationships of dietary intake, toxicity, and survival. Highlights: This is the first prospectively cohort monitoring dietary intake among children with ALL. Several disease risk factors were identified for intakes below and in excess of recommended values. Despite previous publications documenting the sharp rise of obesity during treatment for pediatric ALL, our findings suggest other factors may be responsible for development of obesity other than excess dietary intake alone.